Property P in G-Metric Spaces. (15th July 2010) - Chugh, Renu; Kadian, Tamanna; Rani, Anju; Rhoades, B. E.
Abstract : We prove two general fixed theorems for maps inG -metric spaces and then show that these maps satisfy propertyP .